Кулькова гвинтова передача - Пестунов, В. М.; Лук'яненко, Л. П.; Лукьяненко, Л. П.; Pestunov, V.; Lukianenko, L. (Производственно-издательский комбинат «Патент», 1993)
Винахід відноситься до машинобудування і може знайти широке застосування в приводах подачі металорізальних верстатів. Метою винаходу є розширення кінематичних можливостей. Це досягається тим, що на зовнішній поверхні гвинта перпендикулярно до гвинтової лінії виконані додаткові канавки, призначені для взаємодії з кульками, а сепаратор виконаний з пружного матеріалу. The invention relates to mechanical engineering and can be widely used in feed drives for machine tools. The aim of the invention is to expand the kinematic capabilities. This is achieved by the fact that additional grooves are made on the outer surface of the screw perpendicular to the helical line, intended for interaction with the balls, and the separator is made of an elastic material.
Шариковая винтовая передача
Ball screw transmission